2014
DOI: 10.1021/es5039744
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Oxidative Phosphorylation (OXPHOS) by Hydroxylated Polybrominated Diphenyl Ethers (OH-PBDEs) Present in the Marine Environment

Abstract: Hydroxylated polybrominated diphenyl ethers (OH-PBDEs) are of growing concern, as they have been detected in both humans and wildlife and have been shown to be toxic. Recent studies have indicated that OH-PBDEs can be more toxic than PBDEs, partly due to their ability to disrupt oxidative phosphorylation (OXPHOS), an essential process in energy metabolism. In this study, we determined the OXPHOS disruption potential of 18 OH-PBDE congeners reported in marine wildlife using two in vitro bioassays, namely the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 53 publications
(104 reference statements)
3
43
0
Order By: Relevance
“…However, when comparing the effects of the three substances in the a TMRM assay, which also gives a positive response for uncoupling and narcotic substances, 6OH-BDE90 and PCP both alter the membrane potential in a similar concentration range whereas FCCP proves to be highly more potent (Legradi et al, 2014). In line with our classification analysis based on the significantly regulated genes, where 6OH-BDE90 and PCP from a new sub cluster together next to the polar narcotics ( Figure 9B).…”
Section: Toxiogenomic-based Moa Assignment Of a Chemical With Unknownsupporting
confidence: 76%
See 2 more Smart Citations
“…However, when comparing the effects of the three substances in the a TMRM assay, which also gives a positive response for uncoupling and narcotic substances, 6OH-BDE90 and PCP both alter the membrane potential in a similar concentration range whereas FCCP proves to be highly more potent (Legradi et al, 2014). In line with our classification analysis based on the significantly regulated genes, where 6OH-BDE90 and PCP from a new sub cluster together next to the polar narcotics ( Figure 9B).…”
Section: Toxiogenomic-based Moa Assignment Of a Chemical With Unknownsupporting
confidence: 76%
“…It appears that 6OH-BDE90 and PCP have the potential for both uncoupling and polar narcosis, depending on test conditions (concentration, duration) or test species (Sixt et al, 1995;Schüürmann et al, 1997;Legradi et al, 2014). The findings presented in this study suggest that the toxicogenomic approach is able to elucidate differences in MoA.…”
Section: Toxiogenomic-based Moa Assignment Of a Chemical With Unknownmentioning
confidence: 66%
See 1 more Smart Citation
“…6-OH-BDE-47 (~1.3 μM) has also been shown to cause oxidative stress in the tails of zebrafish larvae using TUNEL staining (Usenko et al, 2012). More recently, in vitro studies with mixtures of OH-BDEs found in the environment were found to disrupt oxidative phosphorylation (through protonophoric uncoupling or inhibition of the electron transport chain) and to have synergistic effects in zebrafish PAC2 cells (Legradi et al, 2014). Additionally 6-OH-BDE-47 has been shown to impact multiple aspects of adult neurogenesis (including cytotoxicity, proliferation, neuronal/oligodendrocyte differentiation) in primary adult neural stem progenitor cells of adult mice (Li et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These effects were more severe than the effects caused by the parent compound, BDE-47 (Dingemans et al, 2010a, 2010b, 2008). Furthermore, 6-OH-BDE-47 exposure during zebrafish larval development has shown thyroid hormone disruption (~1.3 μM) and disrupted energy metabolism (oxidative phosphorylation) (~1 μM) (Legradi et al, 2014; Liu et al, 2015; Usenko et al, 2012; van Boxtel et al, 2008). Adult neurogenesis is also a target of 6-OH-BDE-47 exposure, including effects on neuronal/oligodendrocyte differentiation in primary adult neural stem progenitor cells of adult mice (Li et al, 2013).…”
Section: Introductionmentioning
confidence: 99%